"BIG-OLD LONG LIPS, BIG-OLD JAR NOSE": ANCIENT MESOAMERICAN MONSTERS AND CLOWNS AND THE TRANSFORMATION OF CHRISTIANITY IN EARLY COLONIAL MEXICO. Issue 2 (2022) - Leeming, Ben
Abstract: During the early Colonial period, Native writers, working under the aegis of mendicant friars, composed Christian texts in the Nahuatl language as part of the Roman Catholic Church's efforts to indoctrinate the Indigenous population of New Spain. Yet these Native "ghost-writers" were far from passive participants in the translation of Christianity. Numerous studies since the 1980s have demonstrated how Native writers exerted influence on the presentation of Christianity, in effect "indigenizing" the message and allowing for the persistence of essential elements of the Mesoamerican worldview. This article focuses on descriptions of demons and sinners drawn from Nahuatl-Christian texts and argues that Native writers drew on an ancient Mesoamerican repertoire of imagery involving physical deformity and transgressive behavior (the "monster-clown complex"). In pre-contact times, such imagery was associated with specific figures, including Olmec dwarfs, Maya "fat men, " and comic performers attached to the Mexica royal court. In each of these figures, both physical deformity and humor rendered them powerful, liminal beings often referred to as ritual clowns. By drawing upon this "monster-clown complex, " Native writers transformed what were intended to be terrifying motivators of conversion into something very different: morally neutral, supernaturally powerful, and ultimately essential members of the Mesoamerican sacred realm.